New Korean wave transnational cultural power in the age of social media - Jin, Dal Yong 1964- (University of Illinois Press, 2016)
"The 2012 smash "Gangnam Style" by the Seoul-based rapper Psy capped the triumph of Hallyu , the Korean Wave of music, film, and other cultural forms that have become a worldwide sensation. Dal Yong Jin analyzes the social and technological trends that transformed South Korean entertainment from a mostly regional interest aimed at families into a global powerhouse geared toward tech-crazy youth. Blending analysis with insights from fans and industry insiders, Jin shows how Hallyu exploited a media landscape and dramatically changed with the 2008 emergence of smartphones and social media, designating this new Korean Wave as Hallyu 2.0. Hands-on government support, meanwhile, focused on creative industries as a significant part of the economy and turned intellectual property rights into a significant revenue source. Jin also delves into less-studied forms like animation and online games, the significance of social meaning in the development of local Korean popular culture, and the political economy of Korean popular culture and digital technologies in a global context"--